Integritas Kristen dalam Profesi Pendidikan: Upaya Guru meningkatkan pentingnya Spiritulitas bagi Nara didik - Pasaribu, Jonias (SIKIP: Jurnal Pendidikan Agama Kristen, 2024)
This article discusses the importance of Christian integrity in the education profession, especially in the context of increasing spirituality for students. Professional teachers should strengthen students' spirituality and integrate Christian values into daily learning. Using a qualitative descriptive method with a literature study approach, it can be concluded that Christian integrity is the foundation of character building in the education profession, where teachers' effort is to pay special attention to the importance of spirituality for students. Integrity is a foundation in education, and the role of spirituality in the formation of character and ethics of students must be a reference to continue to be taught. So that teachers have a strategy to increase student spirituality. Christian integrity is introduced as a moral foundation for teachers' actions and teaching. Emphasis is placed on how spirituality can shape students' character and ethics, as well as strategies teachers can use to enhance students' spirituality, including prayer, Bible reading, and other spiritual activities. With a Christian values-centered approach, teachers can be essential in guiding students toward solid spiritual growth and strengthening their integrity in daily life. Keywords:   AbstrakArtikel ini membahas pentingnya peran integritas kristiani dalam profesi pendidikan, khususnya dalam konteks peningkatan spiritualitas bagi naradidik. Guru yang berprofesi harussnya mempunyai tanggung jawab untuk memperkuat spiritualitas siswa dan mengintegrasikan nilai-nilai kristiani dalam pembelajaran sehari-hari. Dengan menggunakan metode deskriptif kualitatif dengan pendekatan studi literatur,maka dapat disimpulkan bahwa integritas kristiani merupakan landasan pembentukan karakter dalam profesi pendidikan, di mana hal ini merupakan upaya guru untuk memberikan perhatian khusus terhadap pentingnya spiritualitas bagi peserta didik. integritas sebagai landasan dalam pendidikan, maka peran spiritualitas dalam pembentukan karakter dan etika peserta didik harus menjadi acuan untuk terus diajarkan. sehingga guru mempunyai strategi untuk meningkatkan spiritualitas siswa. Konsep integritas kristiani diperkenalkan sebagai landasan moral dalam tindakan dan pengajaran guru. Penekanannya ditempatkan pada bagaimana spiritualitas dapat membentuk karakter dan etika siswa, serta strategi yang dapat digunakan guru untuk meningkatkan spiritualitas siswa, termasuk doa, membaca Alkitab, dan kegiatan spiritual lainnya. Dengan pendekatan yang berpusat pada nilai-nilai kristiani, guru dapat memainkan peran penting dalam membimbing siswa menuju pertumbuhan rohani yang kokoh dan memperkuat integritas mereka dalam kehidupan sehari-hari.